* Signifikansi ‘Illat Hukum Dan Hikmah: Signifikansi ‘Illat - Herry Syahbannuddin Nst (STAI Tebing Tinggi Deli, 2021)
Many legal provisions are determined by using the theory of qiyas or the basis ofits 'illat equation. The principle of qiyas is that the legal provisions that have beendescribed in the texts (principles) can be applied to other matters not mentionedin the texts, if there is a similarity of 'illat between the two.It cannot be denied that the reality of Islamic law is dynamic and developsaccording to the developmental guidance of time and place. In other words, thedevelopment of Islamic law, in addition to the demands of society, also cannot beseparated from the role of 'illat as the basis behind tasyri' or legal law. In thehistory of the development of Islamic law, from the beginning until now, it is seenthat 'illat plays a very important role in the development of Islamic law.Reasoning `by using 'illat qiyas is widely used among ushul scholars until now.Many new problems that are not explained in the texts of the Qur'an and al-Sunnah, the legal provisions can be determined textually by using this 'illat qiyas.For this reason, examples of cases related to the application of 'illat qiyas arepresented